2018
DOI: 10.3390/md16120462
|View full text |Cite
|
Sign up to set email alerts
|

Nile Tilapia Derived Antimicrobial Peptide TP4 Exerts Antineoplastic Activity Through Microtubule Disruption

Abstract: Some antimicrobial peptides (AMPs) exhibit anti-cancer activity, acting on cancer cells either by causing membrane lysis or via intracellular effects. While intracellular penetration of AMPs has been shown to cause cancer cell death, the mechanisms of toxicity remain largely unknown. Here we show that a tilapia-derived AMP, Tilapia piscidin (TP) 4, penetrates intracellularly and targets the microtubule network. A pull-down assay identified α-Tubulin as a major interaction partner for TP4, and molecular docking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 48 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…Moreover, other non-lytic pathogen-killing pathways, which involve the targeting of specific cellular factors, have also been reported [ 6 ]. Interestingly, some pathogen-killing activities may also allow AMPs to target cancer cells, and several AMPs have been implicated as promising anticancer agents for various cancers [ 7 , 8 , 9 , 10 , 11 , 12 ]. One such AMP, Tilapia piscidin (TP) 4, was identified in Nile tilapia ( Oreochromis niloticus ) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, other non-lytic pathogen-killing pathways, which involve the targeting of specific cellular factors, have also been reported [ 6 ]. Interestingly, some pathogen-killing activities may also allow AMPs to target cancer cells, and several AMPs have been implicated as promising anticancer agents for various cancers [ 7 , 8 , 9 , 10 , 11 , 12 ]. One such AMP, Tilapia piscidin (TP) 4, was identified in Nile tilapia ( Oreochromis niloticus ) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…One such AMP, Tilapia piscidin (TP) 4, was identified in Nile tilapia ( Oreochromis niloticus ) [ 13 ]. A growing body of literature has shown that a synthesized active segment of TP4 has broad-spectrum antibacterial activities [ 13 , 14 , 15 ] as well as excellent cancer cell-killing activity in different cancer types in vitro and in vivo [ 9 , 10 , 11 , 12 , 16 , 17 ]. Multiple anticancer mechanisms are thought to be involved in AMP-mediated cytotoxicity, including rapid cell membrane disruption at high-dose treatment [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations